2015
DOI: 10.4236/ojf.2015.54036
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Multilocus Heterozygosity on the Longevity of Seedlings Established on Fallen Logs in <i>Picea jezoensis</i> and <i>Abies sachalinensis</i>

Abstract: Seedling establishment on fallen logs is a major regeneration system for tree species in boreal forests. Seedling survival on fallen logs is affected not only by the microsite environment but also by the genetic factors of individuals. To quantify the genetic effects on seedling longevity, we identified seedlings using a number tag system and collected needles of Picea jezoensis and Abies sachalinensis established on fallen logs in spring 2006. Survival or death of each seedling was investigated during 2006-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The decrease in average F is value with life history process might be influenced by inbreeding depression at the growing stages after seedling establishment. Our previous study, based on the same population examined in the present study, indicated that multilocus heterozygosity had an effect on seedling longevity ( Okada et al, 2015 ). Some cross-experiment studies of Picea species have shown that growth in height decreased as the kinship coefficient increased ( Doerksen et al, 2014 ).…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…The decrease in average F is value with life history process might be influenced by inbreeding depression at the growing stages after seedling establishment. Our previous study, based on the same population examined in the present study, indicated that multilocus heterozygosity had an effect on seedling longevity ( Okada et al, 2015 ). Some cross-experiment studies of Picea species have shown that growth in height decreased as the kinship coefficient increased ( Doerksen et al, 2014 ).…”
Section: Discussionsupporting
confidence: 57%
“…DNA was extracted from dried needle leaf samples from 531 individuals using a DNeasy Plant Mini kit (Qiagen). The following 11 microsatellite loci, GC1, GD1, GG3 ( Pfeiffer et al, 1997 ), PaGB3, PgGB5 ( Besnard et al, 2003 ), EATC1E03, EATC2G05 ( Scotti et al, 2002 ), Pj4, Pj8, Pj22 , and Pj24 ( Okada et al, 2015 ) were analyzed using a Multiplex PCR Kit (Qiagen) together with a 3130xl Genetic Analyzer and GeneMapper ver. 4.0 (Thermo Fisher Scientific Inc.).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Not only allele frequencies but also the heterozygosity of an individual is often associated with fitness among a changing environment (e.g., [40]). Correlations have been reported between growth rate and heterozygosity in Populus tremuloides [41] and survivorship and heterozygosity in Picea jezoensis [42]. It has been observed that the heterozygosity of a population influences its productivity, fitness, and stability [40,43,44].…”
Section: Discussionmentioning
confidence: 99%